Gambling: an addictive behavior with health and primary care implications. - Potenza, Marc N; Fiellin, David A; Heninger, George R; Rounsaville, Bruce J; Mazure, Carolyn M (Journal of general internal medicine, 2002)
Over the past several decades, and particularly during the last 10 to 15 years, there has been a rapid increase in the accessibility of legalized gambling in the United States and other parts of the world. Few studies have systematically explored the relationships between patterns of gambling and health status. Existing data support the notion that some gambling behaviors, particularly problem and pathological gambling, are associated with nongambling health problems. The purpose of this article is to provide a perspective on the relationship between gambling behaviors and substance use disorders, review the data regarding health associations and screening and treatment options for problem and pathological gambling, and suggest a role for generalist physicians in assessing problem and pathological gambling. A rationale for conceptualization of pathological gambling as an addictive disorder and a model proposing stress as a possible mediating factor in the relationship between gambling and health status are presented. More research is needed to investigate directly the biological and health correlates associated with specific types of gambling behaviors and to define the role for generalist physicians in the prevention and treatment of problem and pathological gambling.
Keywords: Behavior Therapy; Behavior, Addictive; Clinical Trials as Topic; Comorbidity; Gambling; Heart Arrest; Humans; Mental Health; Primary Health Care; Questionnaires; Risk Factors; Stress, Psychological; Substance-Related Disorders; Suicide